Radical Islamism as a Mode of Production - Masdar Hilmy (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2019)
This article attempts to provide a breakthrough which I call mode of production theory. This theory will be employed to analyze the contemporary phenomenon of radical Islamism. The mode of production theory is meant to bridge the two clashing theoretical paradigms in social sciences and humanities, i.e., Weberian and Marxian. Despite its bridging nature, the paper argues that the two cannot be merged within one single thread. This is because each paradigm has its own epistemological basis which is irreconcilable to one another. Mostly adapted from Marx’s theory, the current theory of the mode of production covers five interrelated aspects, namely social, political, economic, cultural, and symbolic structures. If Marx’s mode of production theory heavily relies on a material and economic basis, the theory used in this paper accommodates cultural and symbolic structures that are Weberian in nature. Although the two paradigms can operate together, the strength of structure (Marxian) overpowers the strength of culture (Weberian). This paper further argues that such cultural-based aspects as ideology, norms, and values play as mobilizing factors under a big schematic dominant structure in the rise and development of the radical Islamist groups.